Food, forests and fields in a Bornean rain forest: towards appropriate agroforestry development - Colfer, C.J.P.; Soedjito, H. (1996)
This article presents the results of a 1979-80 dietary record keeping study carried out in the Uma’ Jalan, Kenyah dayak village of Long Segar, East Kalimantan. After a brief introduction to the people and their context, the chapter describes the dietary recordkeeping study method as useful for determining the foods consumed by forest dwellers. Analysis of the food repertoire, diet and nutrition, and the relative importance of fields and forests as sources of food, is presented, with accompanying tables and figures. The chapter concludes with a call for more risk taking among foresters and ecologists, in trying to communicate more effectively across disciplinary boundaries and to contribute more effectively to development and conservation goals in forested areas.